Effect of (Na, Si, Al, K or Ca) doping on the electronic structure and optoelectronic properties of half-Heusler LiMgN alloy: Ab initio framework. (15th February 2022) - Ziat, Younes; Zarhri, Zakaryaa; Hammi, Maryama; Belkhanchi, Hamza; Ifguis, Ousama; Cano, Andrés Domínguez; Bastos, Alicia Carrillo
Abstract: The effect of (Y Na, Si, Al, K or Ca) - dopant have been investigated on the electronic structure and optoelectronic properties of LiMgN. In the present work, the ab initio is carried out within the full-potential linearized augmented plane wave (FP—LAPW) framework. The generalized gradient approximation with the modified Becke—Johnson potential approximation (TB-mBJ) proposed by Tran and Blaha is applied to LiMgN, in which the M g is being substituted by an amount of 6.25% of ( Na-, Si-, Al-, K-, or Ca- ). The results show that the undoped LiMgN has a band gap of 3.954 eV. Where the band structure and density of states (DOS) analysis exhibit the n-type conductivity when ( Y Si or Al) and the p-type conductivity is predicted when ( Y Na, K or Ca ). The imaginary part of dielectric function ε 2 ( ω ) has been plotted, in which the peaks of ( Na, K and Ca ) shift to the high energy scale thanks to the holes originating from these elements. Also, the absorption coefficient α ( ω ) and reflectivity R ( ω ) are plotted. The α ( ω ) of Si is higher than the others, a peak appeared at around 350 nm in blue-shift. The α ( ω ) of Ca is close to the pure one, from which the Ca doped LiMgN can be considered as transparent material in the visible range. Where the R(ω) of pure LiMgN and Ca -doped LiMgN alloys is of 10% in the visible range. Highlights: The M g is being substituted by an amount of 6.25% of ( N a -, S i -, A l -, K - or C a -) doped LiMgN. The ( S i or A l )- doped LiMgN having n-type conduct, where ( N a, K or C a )- doped LiMgN having p-type conduct. The ε 2 ( ω ) function is discussed, in which the peaks of ( N a, K and C a ) shift to the high energy scale. The C a doped LiMgN can be considered as transparent material in the visible range.